Dramaturgical self-efficacy and opportunity structures for white-collar crime. - Engdahl, Oskar (Crime, Law & Social Change, 2022)
Perceived self-efficacy is often held to be the most focal mechanism of human agency. It has shown strong potential to explain action in multiple areas highly relevant to understanding crime, at least when the concept is formulated in close connection with the conditions that characterize the criminal acts it is supposed to explain. This article introduces the concept in the context of white-collar crime. To advance our understanding of how opportunities for such crime work, self-efficacy is defined with regard to one's ability to control others' impression of financially relevant information, or what is called dramaturgical self-efficacy. The presentation of this concept and its various elements is illustrated with contemporary empirical cases of white-collar crime and is preceded by a discussion of how opportunity structures and perceived self-efficacy have been understood in previous research relevant to the field. The article also discusses how the concept can be further developed with regard to the relationship between motivation and opportunity for white-collar crime.